2019
DOI: 10.1021/acs.chemmater.8b05240
|View full text |Cite
|
Sign up to set email alerts
|

Phytol-Derived Alkyl Side Chains for π-Conjugated Semiconducting Polymers

Abstract: Diketopyrrolopyrrole (DPP)-based semiconducting polymers were synthesized with the alkyl side chains of 3,7,11,7,11, that are derived from phytol, a naturally occurring diterpene alcohol. The properties of these polymers were compared to those of DPP-2-octyldodecyl (DPP-OD), a polymer comprising a conventional branched alkyl side chain having the same number of carbon atoms as TMHDe and TMHD. DPP-TMHDe and DPP-TMHD showed good solubility in organic solvents and had longer effective conjugation lengths than DPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Different alkyl side chains modification strategies ,, are often applied to organic semiconductor systems to improve their solubility and flexibility as well as adjust the molecular microstructure and charge transport behavior. Meanwhile, some researchers also elaborated on the effect of gate dielectrics based on metal or metal oxide surfaces with different alkyl chains length self-assembled monolayers on the device performance and stability of OTFTs. , These results proved that the alkyl chains’ chemical modification strategies in both organic semiconductors and inorganic dielectric layers can significantly influence the device performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different alkyl side chains modification strategies ,, are often applied to organic semiconductor systems to improve their solubility and flexibility as well as adjust the molecular microstructure and charge transport behavior. Meanwhile, some researchers also elaborated on the effect of gate dielectrics based on metal or metal oxide surfaces with different alkyl chains length self-assembled monolayers on the device performance and stability of OTFTs. , These results proved that the alkyl chains’ chemical modification strategies in both organic semiconductors and inorganic dielectric layers can significantly influence the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although some strategies have been taken to optimize PI chemical structures and preparation ways for improving the performance of OTFTs, low-temperature solution processing PI-based gate dielectrics for flexible OTFTs with high mobility (>1 cm 2 /Vs), relatively low operating voltage (<30 V), hysteresis-free behavior, and high operational stability remain a priority in this field of research. 14,28−32 Different alkyl side chains modification strategies 20,33,34 are often applied to organic semiconductor systems to improve their solubility and flexibility as well as adjust the molecular microstructure and charge transport behavior. Meanwhile, some researchers also elaborated on the effect of gate dielectrics based on metal or metal oxide surfaces with different alkyl chains length self-assembled monolayers on the device performance and stability of OTFTs.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of branched side chains on their packing orientation is extensively studied by many research groups. Wang and colleagues synthesized DPP-based polymers P1 , P2 , and P3 , where P1 was connected with branched 2-octyldodecyl (OD) and P2 and P3 with linear 3,7,11,15-tetramethylhexadec-2-en-1-yl (TMHDe) and 3,7,11,15-tetramethylhexadecyl (TMHD), respectively (Figure ). The GIXD characterization demonstrated that the polymers with linear side chains ( P2 and P3 ) were self-organized in an edge-on manner due to the strong polymer packing.…”
Section: Side Chainsmentioning
confidence: 99%
“…[11][12][13] Some functional side chains were also incorporated into polymers to fabricate devices with a specic function. [14][15][16] In recent years, numerous lactam-and imide-functionalized polymers with high carrier mobilities have been reported. Considering the mobility of silicon FETs, which is around 1 cm 2 V À1 s À1 , the ultra-high hole mobility of over 14.0 cm 2 V À1 s À1 and the balanced hole/electron mobilities around 6.5 cm 2 V À1 s À1 achieved by polymer semiconductors have made considerable progress.…”
Section: Introductionmentioning
confidence: 99%